2013
DOI: 10.1002/jso.23476
|View full text |Cite
|
Sign up to set email alerts
|

Ability of FDG‐PET/CT in the detection of gallbladder cancer

Abstract: Diagnosis of malignancy or benignity of suspicious gallbladder lesions is accurately made with FDG PET/CT, allowing a precise staging of GBC due to its ability to identify unsuspected metastatic disease. SUVmax has a complementary role in addition to visual analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…In one study of 108 patients undergoing PET before reresection, there was useful signal take‐up in patients with disseminated disease, particularly in those with T2 status. Another study found altered management in 22 per cent of patients based on PET results, with accuracy reaching 100 per cent for disseminated disease when used in a restaging setting. Although data are currently based on few series of incidental gallbladder cancer, these suggest that PET–CT has a role before reresection in any T1b cancer and above for detection of disseminated disease, and for ruling out local residual disease in T1b cancers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study of 108 patients undergoing PET before reresection, there was useful signal take‐up in patients with disseminated disease, particularly in those with T2 status. Another study found altered management in 22 per cent of patients based on PET results, with accuracy reaching 100 per cent for disseminated disease when used in a restaging setting. Although data are currently based on few series of incidental gallbladder cancer, these suggest that PET–CT has a role before reresection in any T1b cancer and above for detection of disseminated disease, and for ruling out local residual disease in T1b cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Another study found altered management in 22 per cent of patients based on PET results, with accuracy reaching 100 per cent for disseminated disease when used in a restaging setting. Although data are currently based on few series of incidental gallbladder cancer, these suggest that PET–CT has a role before reresection in any T1b cancer and above for detection of disseminated disease, and for ruling out local residual disease in T1b cancers. One study advised against undertaking redo surgery in patients with T1b cancers if PET–CT findings were negative, as the likelihood of finding residual disease was very low.…”
Section: Resultsmentioning
confidence: 99%
“…Data from high‐volume centres demonstrating that up to 26% of GBC patients will have axial LN involvement (aortocaval/coeliac) that would negate any benefit of radical surgery indicate that aortocaval LN sampling should be performed routinely at the initiation of the operation . Although periportal regional LN (N1) involvement does not contraindicate radical resection, it is a very poor prognostic indicator, and therefore the presence of an institutional neoadjuvant therapy protocol for locally advanced GBC may indicate that pathologic confirmation of regional disease should discontinue the immediate plan for up‐front resection in favour of the prospective evaluation of pre‐resection chemotherapy and/or chemoradiotherapies …”
Section: Evaluation and Management Of A Gallbladder Massmentioning
confidence: 99%
“…32,33 Although periportal regional LN (N1) involvement does not contraindicate radical resection, it is a very poor prognostic indicator, and therefore the presence of an institutional neoadjuvant therapy protocol for locally advanced GBC may indicate that pathologic confirmation of regional disease should discontinue the immediate plan for up-front resection in favour of the prospective evaluation of pre-resection chemotherapy and/or chemoradiotherapies. 34 Laparoscopic and open approaches to definitive resection Minimally invasive resection of intact GBC has been performed at specialized expert centres. These centres have reported safety and feasibility outcome data for T1b, T2 and even T3 tumours that rival the outcomes of open surgery, 35 but no randomized studies have objectively compared the minimally invasive and open surgery approaches.…”
Section: Intraoperative Ln Evaluationmentioning
confidence: 99%
“…Though ultrasonography (USG) is most widely used initial screening as well diagnostic tool, it lacks sensitivity and specificity for early cancer. Other preferred investigations are endoscopic ultrasound (EUS), computed tomography (CT) scan, magnetic resonance cholangiopancreatography (MRCP) and fluorodeoxyglucose positron emission tomography (FDG-PET) [9]. Although there is currently no single tumor marker helping clinch diagnosis, promising one include cancer antigen (CA) 242, CA-125, and CA-19-9.…”
Section: Introductionmentioning
confidence: 99%